1988
DOI: 10.1182/blood.v71.4.1113.bloodjournal7141113
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABH and X (Lex) antigens on platelets and lymphocytes

Abstract: We used a panel of reagents, polyclonal and monoclonal antibodies, and lectins to define the expression of the ABH- and Lewis-related specificities on platelets and lymphocytes. We also determined the expression of the alpha 2- and alpha 3-L-fucosyltransferases necessary for their biosynthesis. The antigens that could be detected by immunofluorescence and Western blot analysis were based on type 2 monofucosylated structures. Antibodies directed toward types 1, 3, and 4 ABH-, X- and Lewis-related antigenic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…RH blood grouping categorizes in two phenotypes D+ and D-depending on the presence or absence of D protein epitopes (16)(17)(18). ABO histo-blood group antigens have been found in RBC's surface lymphocytes, as well as many tissue organs, mucosal surfaces, and exocrine secretions (13,(19)(20)(21)(22)(23). The human body produces antibodies against the missing ABO histo-blood group antigens resulting in the production of anti-A and/or anti-B antibodies (13,24).…”
Section: Discussionmentioning
confidence: 99%
“…RH blood grouping categorizes in two phenotypes D+ and D-depending on the presence or absence of D protein epitopes (16)(17)(18). ABO histo-blood group antigens have been found in RBC's surface lymphocytes, as well as many tissue organs, mucosal surfaces, and exocrine secretions (13,(19)(20)(21)(22)(23). The human body produces antibodies against the missing ABO histo-blood group antigens resulting in the production of anti-A and/or anti-B antibodies (13,24).…”
Section: Discussionmentioning
confidence: 99%
“…Also, by immunofluorescence, the IgG antibodies from individuals with high anti-A titres have been shown to react with blood group A 1 but not A 2 platelets (Skogen et al, 1988). Furthermore, it was found that an anti-A antibody strongly stained bands around 140-130 kDa under reducing conditions; weaker bands ranging between 160 and 60 kDa were also labelled (Mollicone et al, 1988). These investigators suggested that the major band could correspond to GPIb, but it was not further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic determinants have been considered to be associated with glycolipids rather than glycoproteins (Dunstan & Mansbach, 1985). Never-theless, in two recent reports anti-A antibodies were found to react with platelet glycoproteins with an approximate molecular weight of 130-140 kDa but not further characterized (Mollicone et al, 1988;Holgersson et al, 1990). In another study, blood group A determinants were assigned to GPIb, IIa and IIIa (Santoso et al, 1991).…”
mentioning
confidence: 99%
“…ABH-active gp120 can be produced in vitro by propagating HIV in cell lines expressing the appropriate glycosyltransferases (280). ABH-active HIV can also be produced by propagating HIV in lymphocytes of a known ABO type (280,281), despite the reported absence of ABH on lymphocyte glycoproteins (282). However, lymphocytes adsorb ABH-active GSLs from plasma (283).…”
Section: Hivmentioning
confidence: 99%